Co-ingestion of carbohydrate and whey protein isolates enhance PGC-1α mRNA expression: a randomised, single blind, cross over study - Hill Karen M; Stathis Christos G; Grinfeld Esther; Hayes Alan; McAinch Andrew J (Taylor & Francis Group, 2013)
Abstract Background Whey protein isolates (WPI) supplementation is known to improve resistance training adaptations. However, limited information is available on the effects of WPI plus carbohydrate (CHO) supplementation on endurance training adaptations. Method Six endurance trained male cyclists and triathletes (age 29 ± 4 years, weight 74 ± 2 kg, VO2 max 63 ± 3 ml oxygen. kg-1. Min-1, height 183 ± 5 cm; mean ± SEM) were randomly assigned to one of two dietary interventions in a single blind cross over design; CHO or CHO + WPI. Each dietary intervention was followed for 16 days which included the last 2 days having increased CHO content, representing a CHO loading phase. The dietary interventions were iso-caloric and carbohydrate content matched. On completion of the dietary intervention, participants performed an exercise bout, consisting of cycling for 60 min at 70% VO2 max, followed by time trial to exhaustion at 90% VO2 max and recovered in the laboratory for 6 hours. Blood samples and muscle biopsies were taken at various time points at rest and through the exercise trial and recovery. Results Compared to CHO, CHO + WPI increased plasma insulin during recovery at 180 mins (P < 0.05) and peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1α) mRNA expression at the end of 6 hours of recovery (P < 0.05). Muscle glycogen did not differ between the two trials. Conclusion This study showed co-ingestion of CHO + WPI may have beneficial effects on recovery and adaptations to endurance exercise via, increased insulin response and up regulation of PGC-1α mRNA expression.